CircNet: a database of circular RNAs derived from transcriptome sequencing data. Issue Volume 44:Issue D1(2016) (7th October 2015) - Liu, Yu-Chen; Li, Jian-Rong; Sun, Chuan-Hu; Andrews, Erik; Chao, Rou-Fang; Lin, Feng-Mao; Weng, Shun-Long; Hsu, Sheng-Da; Huang, Chieh-Chen; Cheng, Chao; Liu, Chun-Chi; Huang, Hsien-Da
Abstract: Circular RNAs (circRNAs) represent a new type of regulatory noncoding RNA that only recently has been identified and cataloged. Emerging evidence indicates that circRNAs exert a new layer of post-transcriptional regulation of gene expression. In this study, we utilized transcriptome sequencing datasets to systematically identify the expression of circRNAs (including known and newly identified ones by our pipeline) in 464 RNA-seq samples, and then constructed the CircNet database (http://circnet.mbc.nctu.edu.tw/ ) that provides the following resources: (i) novel circRNAs, (ii) integrated miRNA-target networks, (iii) expression profiles of circRNA isoforms, (iv) genomic annotations of circRNA isoforms (e.g. 282 948 exon positions), and (v) sequences of circRNA isoforms. The CircNet database is to our knowledge the first public database that provides tissue-specific circRNA expression profiles and circRNA–miRNA-gene regulatory networks. It not only extends the most up to date catalog of circRNAs but also provides a thorough expression analysis of both previously reported and novel circRNAs. Furthermore, it generates an integrated regulatory network that illustrates the regulation between circRNAs, miRNAs and genes.